Climate Change and Its Impact on Agriculture Sector: Evidence from Western Nepal - Koirala, Sunita; Khatiwada, Kabita; Karki, Supendra; Ghimire, Diya (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Climate change has emerged as a major global challenge, disproportionately affecting agricultural communities in developing countries like Nepal. This study assessed farmers’ knowledge and perceptions of climate change and its impact on agriculture in western Nepal. Method: A cross-sectional survey was conducted among 1,046 respondents from eight wards of the Gandaki district using a structured questionnaire. Data were analysed using descriptive statistics in SPSS v26. Result: The average age of respondents was 56.05 years, and 93.4% depended primarily on agriculture, although only 18.1% had received formal agricultural training. Educational attainment was low, with 21% being illiterate and 32.4% having only informal education. The majority of respondents (67.8%) had heard about climate change, with radio (65%) and television (53.6%) serving as the most common information sources. Farmers reported experiencing shifting climatic conditions, including irregular rainfall, rising temperatures, and decreased water availability, which they perceived as affecting crop yields, livestock productivity, and overall agricultural stability. Conclusion: Overall, farmers are experiencing climatic changes but lack sufficient knowledge and adaptive strategies. The findings highlight the need for targeted climate education, strengthened agricultural extension services, and improved rural infrastructure to enhance resilience and support sustainable agricultural livelihoods in western Nepal.